Brigadoon - Loewe, Frederick 1901-1988 (Warner Bros. Home Entertainment, 2017)
Two American hunters lost in the highlands of Scotland stumble upon a small town not listed on any map
Based on the musical play by Frederick Loewe, lyrics by Alan Jay Lerner
DTS 5.1, wide screen 2.35:1
Keywords: Loewe, Frederick / 1901-1988 / Film adaptations; Man-woman relationships / Drama; Brigadoon (Scotland : Imaginary place) / Drama; Loewe, Frederick / 1901-1988; Brigadoon (Scotland : Imaginary place); Man-woman relationships; Drama; Fantasy films; Feature films; Fiction films; Film adaptations; Musical films; Romance films; Films d'amour; Films fantastiques; Films musicaux; Adaptations cinématographiques; Films de fiction; Film; Blu-Ray-Disc